2014
DOI: 10.1089/vbz.2013.1304
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasmosis in Natural Populations of Ungulates in France: Prevalence and Spatiotemporal Variations

Abstract: Toxoplasmosis is characterized by a complex epidemiology. The risk of infection for humans depends on their contact with infective oocysts in a contaminated environment and on the amount of tissue cysts located within consumed meat. Unfortunately, the prevalence of tissue cysts is largely unknown for game species. Although herbivorous game species are a source of infection for humans, the level of infection found in wildlife can also be used to estimate environmental contamination. The aim of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
(58 reference statements)
3
10
0
Order By: Relevance
“…The high level of the mean apparent seroprevalence observed in our study (43.7 %) was in accordance with this general pattern and the results of several other studies in Europe 43.7 % in France, 52 % in Belgium, 21.2 % in Spain, 33.9 % in Norway, and 34 % in Sweden (Vikøren et al 2004;Gauss et al 2006;Malmsten et al 2011;De Craeye et al 2011;Gotteland et al 2014). By contrast, the prevalence of C. abortus in wild mammals is poorly documented (Pospischil et al 2012).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The high level of the mean apparent seroprevalence observed in our study (43.7 %) was in accordance with this general pattern and the results of several other studies in Europe 43.7 % in France, 52 % in Belgium, 21.2 % in Spain, 33.9 % in Norway, and 34 % in Sweden (Vikøren et al 2004;Gauss et al 2006;Malmsten et al 2011;De Craeye et al 2011;Gotteland et al 2014). By contrast, the prevalence of C. abortus in wild mammals is poorly documented (Pospischil et al 2012).…”
Section: Discussionsupporting
confidence: 92%
“…We showed that roe deer exposure to T. gondii varied among years in relation to rainfall and temperature. Interannual variability in seroprevalence as a function of yearly rainfall and temperature has also been described in two other roe deer populations in France (Gotteland et al 2014). These results thus confirm previous observations, indicating that the survival of oocysts, and thus the contact between roe deer and infectious T. gondii, is highest during wet years with mild winters (Lélu et al 2012).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Another possible source of heterogeneity could have been the age of the animal tested. Several authors recorded higher seroprevalence in older animals, claiming that this might reflect a longer period of exposure with an increase probability of acquiring the infestation (Almería et al., 2018; Gotteland et al., 2014; Heddergott et al., 2018; Sevila et al., 2014; Vikøren et al., 2004). However, we could not study the age‐prevalence pattern because not all the studies reported information about animal age or they did not apply homogenous criteria for age classification.…”
Section: Discussionmentioning
confidence: 99%
“…The highest seroprevalence observed in 2009 was not related to a particular colony, since no significant differences in seroprevalence were observed among colonies that year, and the variations seemed to be independent of the origin of the diet. Temporal, year-to-year variations have also been explained by the effect of variable meteorological conditions on the level of infection in domestic [ 26 ] and wild species [ 27 ]. Although seroprevalence fluctuation in wildlife populations has been studied [ 28 ], further studies will be needed to explain seroprevalence of T .…”
Section: Discussionmentioning
confidence: 99%